Pembelajaran Tradisional dalam Pandangan Santri: Traditional Learning from the Perspective of Islamic Boarding School Students - Sarwan Sarwan (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2007)
Traditional Islamic education faces tensions between preserving heritage and integrating modern methods, yet many pesantren maintain classical systems despite contemporary pressures. This study explores how traditional learning systems operate and why students remain attracted to them at Madrasah Diniyah PP. Salafiyah Curahkates, Jember. Using a descriptive qualitative case study approach, data were collected through participant observation, unstructured interviews, and documentation, then analyzed using Miles and Huberman’s interactive model. The findings reveal that the learning system comprises four key components: objectives focused on moral-religious formation; local curricula based on classical kitab (manhaj); sorogan (individual), bandongan (lecture), and mudzakarah (discussion) methods; and oral, written, and behavioral evaluations. Students are strongly interested because these traditional methods foster barakah (spiritual blessing), direct correction from teachers, mastery learning through kitab completion, and close student-kyai relationships. The study concludes that traditional learning persists not as a relic but as a valued pedagogical choice. Recommendations include systematically documenting local manhaj and more formally integrating character assessment while preserving sorogan and bandongan as core identity markers. Pendidikan Islam tradisional menghadapi ketegangan antara mempertahankan warisan dan mengintegrasikan metode modern, namun banyak pesantren tetap mempertahankan sistem klasik. Penelitian ini mengeksplorasi bagaimana sistem pembelajaran tradisional beroperasi dan mengapa santri tetap tertarik di Madrasah Diniyah PP. Salafiyah Curahkates, Jember. Menggunakan pendekatan kualitatif deskriptif dengan jenis studi kasus, data dikumpulkan melalui observasi partisipasi, wawancara tidak terstruktur, dan dokumentasi, kemudian dianalisis dengan model Miles dan Huberman. Temuan menunjukkan sistem pembelajaran terdiri dari empat komponen: tujuan pembentukan moral-keagamaan; kurikulum lokal berbasis kitab kuning (manhaj); metode sorogan, bandongan, dan mudzakarah; serta evaluasi lisan, tulisan, dan perilaku. Santri sangat tertarik karena metode tradisional ini memberikan keberkahan, koreksi langsung dari ustadz, penguasaan tuntas melalui khataman kitab, serta hubungan dekat dengan kyai. Kesimpulannya, pembelajaran tradisional bertahan bukan sebagai peninggalan tetapi pilihan pedagogis yang dihargai. Rekomendasi mencakup pendokumentasian manhaj lokal secara sistematis dan pengintegrasian penilaian karakter yang lebih formal tanpa meninggalkan sorogan dan bandongan sebagai penanda identitas utama.